Bells Palsy as a Possible Complication of Hepatitis B Vaccination in A Child - Alp, Handan; Tan, Hüseyin; Orbak, Zerrin (Journal of Health, Population and Nutrition, 2009)
Bell's Palsy is the sudden onset of unilateral temporary paralysis of facial muscles resulting from seventh cranial nerve dysfunction. Presented here is a two-year old female patient with right peripheral facial palsy following hepatitis B vaccination. Readers' attention is drawn to an uncommon cause of Bell's Palsy, as a rare complication of hepatitis B vaccination. J Health Popul Nutr 2009 Oct; 27(5):707-708